Investigation of genotoxic and apoptotic effects of zirconium oxide nanoparticles (20 nm) on L929 mouse fibroblast cell line. (25th December 2018) - Atalay, Hande; Çeli̇k, Ayla; Ayaz, Furkan
Abstract: In recent years, advances in nano-scale technology have led to the use of nanoparticles in almost all areas of life. Nanoparticles (NP) have been acknowledged as one of the emerging environmental threats; however, studies in different components of environment are limited. Among the available nanoparticles, zirconium oxide nanoparticles are widely used in tooth coating and cosmetic products. In this study, three different concentrations of 20 nM Zirconium Oxide nanoparticles were used to investigate the genotoxic and apoptotic effects in vitro conditions by single cell gel electrophoresis (Comet) and flow cytometry methods on L929 Mouse Fibroblast cell line. In this study, we aimed to decipher whether Zirconium Oxide nanoparticles had genotoxic and apoptotic effects on fibroblast cells or not. The relationship between the apoptotic effect and the genotoxic effect was examined. Three different concentrations (50 μg/ml, 100 μg/ml and 150 μg/ml) of 20 nM Zirconium Oxide nanoparticles were used on L929 cells in order to determine the relationship between apoptotic and genotoxic parameters. Our results support that Zirconium Oxide nanoparticles induced DNA damage and apoptosis at all used concentrations. In vivo studies are currently conducted to further evaluate the cytotoxic effect of these nanoparticles. Highlights: ZrO2 nanoparticles caused a significant genotoxic damage in a dose dependent manner. There is correlation rates between comet parameters. It was determined that ZrO2 nanoparticles caused apoptotic and necrotic effects in dose dependent. This study indicate that comet and flow cytometry methods is complement eachother.